Developing a Qualitative Framework for Sharing Managerial Experiences Using a Phenomenological Approach (Case Study: Islamic Azad University) - Asri, Saba; Shariatmadari, Narges; AfzalKhani, Maryam (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The present study was conducted with the aim of explaining a conceptual model for sharing managerial experiences based on the lived experiences of middle managers at Islamic Azad Universities in Semnan Province.Methods and Materials: In terms of purpose, this research is applied, and in terms of nature, it is qualitative with an exploratory approach, employing a phenomenological method. The participants consisted of middle managers from Islamic Azad Universities in Semnan Province, who were selected through purposive sampling. Data saturation was achieved after conducting 17 semi-structured interviews. The data were analyzed using Colaizzi’s seven-step phenomenological method.Findings: The results of the data analysis led to the extraction of 128 initial codes (indicators), which, after processes of comparison and integration, were organized into 27 sub-themes and 7 main themes. The main themes included: the nature and characteristics of managerial experience (4 sub-themes, 20 indicators), managers’ perceptions and attitudes toward experience sharing (4 sub-themes, 20 indicators), individual factors influencing the sharing of managerial experiences (3 sub-themes, 12 indicators), organizational contexts and requirements (4 sub-themes, 20 indicators), operational mechanisms for sharing managerial experiences (4 sub-themes, 17 indicators), challenges and barriers to sharing managerial experiences (4 sub-themes, 19 indicators), and the outcomes of sharing managerial experiences (4 sub-themes, 20 indicators).Conclusion: The findings indicated that sharing managerial experiences is a multidimensional and context-dependent phenomenon influenced by the interaction of individual, organizational, and cultural factors. Its effective realization requires the provision of appropriate structural contexts, the strengthening of managers’ motivation and professional trust, and the design of both formal and informal mechanisms for experience transfer. The results of this study can serve as a scientific basis for policymaking, improving organizational learning systems, and enhancing managerial effectiveness in Islamic Azad Universities.